Necessary risks : challenges privileged people need to face - Ott, Teri McDowell (Minneapolis, MN : Fortress Press, 2022)
In Necessary Risks, Teri McDowell Ott explores her wrestling, as a privileged white Christian woman, with ten risks and the underlying systems and structures that need to be changed. Such risks, she argues, transform individuals and communities, creating a path toward a more equitable and just world.
Introduction: On fear -- Risk going -- Risk staying -- Risk learning -- Risk teaching -- Risk following -- Risk leading -- Risk listening -- Risk speaking -- Risk failing -- Risk succeeding.
Online resource; title from digital title page (viewed on January 28, 2022).
JSTOR
Keywords: Christianity and justice; Social justice -- Religious aspects -- Christianity; Church work with minorities; Justice -- Aspect religieux -- Christianisme; Pastorale des minorités.; Ethics; RELIGION; Christian Ministry; Christian Life; Christianity and justice; Church work with minorities; Social justice -- Religious aspects -- Christianity; Electronic books